Critical Thinking Development through Project-Based Learning in English Language Classes - Muhammad Robi; Ali Usman; Arif Eka Kurnianto (Gema Cendekia Institute, 2026)
This study investigates the effectiveness of Project-Based Learning in developing critical thinking skills in English language classes. It addresses the need for instructional approaches that promote higher-order thinking alongside language proficiency. A mixed-methods design was used to examine cognitive, behavioral, and reflective outcomes of Project-Based Learning implementation. Quantitative data were collected through pre-test and post-test measures of critical thinking, while qualitative data were obtained from classroom observations, learner reflections, interviews, and analysis of project artifacts. The findings show a significant improvement in learners’ critical thinking abilities after participation in project-based instruction. Learners demonstrated stronger skills in analysis, evaluation, and reasoned argumentation. Qualitative evidence indicates that students became more engaged, autonomous, and reflective during the learning process. Project tasks promoted problem solving, collaboration, and decision making, which supported deeper cognitive engagement. Teacher facilitation and structured collaboration played a key role in guiding learners’ reasoning processes. Language proficiency affected the clarity of critical thinking expression, highlighting the need for linguistic scaffolding in cognitively demanding tasks. The study concludes that Project-Based Learning is an effective framework for integrating critical thinking into English language education while supporting communicative competence.